ANALYSIS OF NUMERACY LITERACY SKILLS OF INTROVERTED AND EXTROVERTED LEARNERS IN SOLVING SPLDV - Suistiani, Suistiani; Suastika, I Ketut; Hariyani, Sri (Universitas Muhammadiyah Ponorogo, 2025)
The focus of this research is to analyse the numeracy literacy ability in solving System of Linear Equations Two Variables (SPLDV) problems in terms of students' personality. The approach used in this research is descriptive qualitative. The subjects taken were two students of class VIII SMP PGRI 4 Kalipare. Subjects in this study were determined using a questionnaire. Data collection techniques in the form of tests and interviews. Based on the results of the study, it shows that students with introverted personality types are able to meet the three indicators of numeracy literacy skills, namely solving problems using various numbers and symbols related to mathematics; analysing information presented in various images (graphs, tables, charts and so on); and interpreting the results of these analyses to make predictions and decisions. However, extroverted learners' personality type is only able to present one indicator of numeracy literacy, namely analysing information presented in various images (graphs, tables, charts and so on)